Cyclic RGD peptides interfere with binding of the Helicobacter pylori protein CagL to integrins αvβ3 and α5β1 - Conradi, Jens; Huber, Sylwia; Gaus, Katharina; Mertink, Felix; Royo Gracia, Soledad; Strijowski, Ulf; Backert, Steffen; Sewald, Norbert (Amino Acids, 2012)
The human pathogen Helicobacter pylori that may cause different gastric diseases exploits integrins for infection of gastric cells. The H. pylori protein CagL present on the outer region of the type IV secretion pilus contains an RGD sequence (-Arg-Gly-Asp-) that enables binding to cells presenting integrins α5β1 and αVβ 3. This interaction can be inhibited with conformationally designed cyclic RGD peptides derived from the CagL epitope -Ala-Leu-Arg-Gly-Asp-Leu-Ala-. The inhibition of the CagL-αVβ3 interaction by different RGD peptides strongly suggests the importance of the RGD motif for CagL binding. CagL point mutants (RAD, RGA) show decreased affinity to integrin αVβ3. Furthermore, structure-activity relationship studies with cyclic RGD peptides in a spatial screening approach show the distinct influence of the three-dimensional arrangement of RGD motif on the ability to interfere with this interaction. Resulting from these studies, similar structural requirements for the CagL epitope as previously suggested for other ligands of integrin αVβ3 are proposed. © 2011 Springer-Verlag.
Created from Fastlane, Scopus look-up
Keywords: α; CagL; Integrins; RGD peptides; SAR studies